2018
DOI: 10.1186/s12878-018-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cytopenias in both HAART and HAART naïve HIV infected adult patients in Ethiopia: a cross sectional study

Abstract: BackgroundIn individuals infected with HIV, hematological abnormalities are common and are associated with increased risk of disease progression and death. However, the profile of hematological abnormalities in HIV infected adult patients is not known in Ethiopia. Thus, the aim of this study was to assess the hematological manifestations of HIV infection and to identify the factors associated with cytopenias in both HAART and HAART naïve HIV infected adult patients in Ethiopia.MethodWe conducted a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 24 publications
17
40
1
Order By: Relevance
“…There are no published reports available from Frenchspeaking countries in the eastern and southern sub-Saharan African region. These countries include: Ethiopia (10 reports); [6][7][8][9][10][11][12][13][14][15] Malawi (1 report); [16] SA (6 reports); [17][18][19][20][21] Rwanda (1 report); [22] Tanzania (1 report); [23] Uganda (4 reports); [24][25][26][27] and Zimbabwe (1 report). [19] The size of the cohorts ranged from 30 -15 030 patients.…”
Section: Haematological Abnormalitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…There are no published reports available from Frenchspeaking countries in the eastern and southern sub-Saharan African region. These countries include: Ethiopia (10 reports); [6][7][8][9][10][11][12][13][14][15] Malawi (1 report); [16] SA (6 reports); [17][18][19][20][21] Rwanda (1 report); [22] Tanzania (1 report); [23] Uganda (4 reports); [24][25][26][27] and Zimbabwe (1 report). [19] The size of the cohorts ranged from 30 -15 030 patients.…”
Section: Haematological Abnormalitiesmentioning
confidence: 99%
“…Severe cytopenias, especially anaemia and thrombocytopenia, are associated with increased morbidity and poorer quality of life. [7,10,17] HIVassociated haematological abnormalities should be managed appropriately by healthcare providers. [4,5] The diagnosis and treatment of haematological abnormalities in HIV-infected individuals have been comprehensively reviewed elsewhere.…”
Section: Haematological Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A pancytopenia was present in 11.2% A recent South African study showed that severe anemia is inversely related to cART exposure 10 while other studies have shown that cART improves anemia 8,11 and that increase in CD4 count correlates with improvement of anemia. 12 In this study however, almost one third of patients were virally suppressed and 12.6% of patients had CD4 counts of >350 cells/µL. However, the predominant causes of severe anemia in the group of patients with CD4 counts of >350 cells/µL were not due to the immune-dysregulating effects of HIV but rather due to causes which may be present in patients with adequate immune reconstitution-namely PRCA (which may be cART drug related), nutritional deficiency, and BM infiltration.…”
mentioning
confidence: 99%